2019
DOI: 10.3390/ijms20051205
|View full text |Cite
|
Sign up to set email alerts
|

A Prediction Model for Preoperative Risk Assessment in Endometrial Cancer Utilizing Clinical and Molecular Variables

Abstract: The utility of comprehensive surgical staging in patients with low risk disease has been questioned. Thus, a reliable means of determining risk would be quite useful. The aim of our study was to create the best performing prediction model to classify endometrioid endometrial cancer (EEC) patients into low or high risk using a combination of molecular and clinical-pathological variables. We then validated these models with publicly available datasets. Analyses between low and high risk EEC were performed using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 47 publications
1
14
0
Order By: Relevance
“…4000 genome sequencing platform employing 150 bp paired-end sequencing by synthesis chemistry was used. All library preparation and sequencing procedures were performed in the Genome Core Facility of the University of Iowa Institute of Human Genetics 27 .…”
Section: Methodsmentioning
confidence: 99%
“…4000 genome sequencing platform employing 150 bp paired-end sequencing by synthesis chemistry was used. All library preparation and sequencing procedures were performed in the Genome Core Facility of the University of Iowa Institute of Human Genetics 27 .…”
Section: Methodsmentioning
confidence: 99%
“…Rather, our aim was to assess the genetic background of patients with endometrial and ovarian cancer that we diagnose and treat, and compare them with the genetic background of patients with the same cancer types in TCGA. The motivation of this study stemmed from the need to validate a prediction model of clinical outcomes that integrated clinical, pathological, and diverse molecular data: gene and miRNA expression, gene copy number and somatic mutations [ 2 , 3 ]. The validation of these prediction models in TCGA datasets was not ideal, so we wanted to investigate possible reasons for this discordance.…”
Section: Discussionmentioning
confidence: 99%
“…Although TCGA and other publicly available datasets have made these validations much simpler, the limitations of doing so have yet to be fully addressed. For example, in our previous studies designed to predict clinical outcomes by integrating clinical, pathological and molecular features of patients with cancer, we found that the best prediction models, developed using our internal patient cohort (University of Iowa), performed 10–20 percentage points worse in TCGA datasets [ 2 , 3 ]. Based on the characteristics of our population (northern European origin), it was obvious that our patients’ backgrounds seemed to be more homogeneous than the population from which TCGA derived their datasets.…”
Section: Introductionmentioning
confidence: 99%
“…Of the 193 patients identified in the original HGSC panel, we were able to obtain 112 tumor tissues with sufficient RNA yield and quality for analysis [ 16 ]. Similarly, of the 126 patients identified in the original endometrial endometrioid cancer panel, we were able to obtain 62 primary tumor tissues with sufficient RNA yield and quality for analysis [ 17 ]. From the 20 original normal fallopian tube samples, 12 had sufficient RNA yield and quality for analysis [ 16 ] ( Figure 1 ).…”
Section: Methodsmentioning
confidence: 99%